Effect of expiratory muscle training on peak cough flow in children and adolescents with cystic fibrosis: A randomized controlled trial. Issue 5 (26th January 2021) - Emirza, Cigdem; Aslan, Goksen Kuran; Kilinc, Ayse Ayzit; Cokugras, Haluk
Abstract: Background: Cough is an important defense and airway clearance mechanism for removing thick and viscous secretions in cystic fibrosis (CF). The primary aim of this study was to investigate the effect of expiratory muscle training (EMT) on peak cough flow (PCF) and secondly on respiratory muscle functions, functional exercise capacity, and quality of life (QoL) in CF. Methods: Thirty patients were randomized as training and sham groups. Both groups were trained with the EMT protocol, which involved twice per day for at least 5 days per week for 6 weeks. The training intensity in the training group was 30% of the maximal expiratory pressure (MEP). In the sham group, it remained at the lowest pressure (5 cmH2 O). The primary outcome was PCF. The secondary outcomes were MEP, maximal inspiratory pressure (MIP), spirometric measures, six‐minute walking distance (6MWD), and QoL (Cystic Fibrosis Questionnaire‐Revised). Results: Twenty‐eight patients completed the study. Changes in PCF ( p  = .041) and MEP ( p  = .003) were higher in the training group than the sham group. Also, treatment burden ( p  = .008), digestive symptoms ( p  = .019), and vitality ( p  = .042) in QoL were more improved in the training group. MIP ( p  = .028) and 6MWD ( p  = .035) changed significantly only in the training group. Spirometric measurements did not change ( p  > .05). Conclusions: The results of the study show that EMT could improve PCF, MEP, treatment burden, digestive symptoms, and vitality domains of QoL in patients with CF. Moreover, MIP and functional exercise capacity improved in the training group with EMT.